2005
DOI: 10.2151/jmsj.83a.137
|View full text |Cite
|
Sign up to set email alerts
|

Possible Effect of Anthropogenic Aerosol Deposition on Snow Albedo Reduction at Shinjo, Japan

Abstract: We observed broadband snow albedos in the visible and the near infrared spectral regions with snow pit works of several-day intervals, during the winters of 2001/2002 and 2002/2003 at Shinjo, Japan. We examined the dependence of albedos on snow grain size and on concentration of snow impurities, comparing observations and theoretical calculations using a radiative transfer model for atmosphere-snow system. The comparisons revealed that the snow was contaminated by strong absorptive impurities such as soot add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…R m of the snow samples varied considerably from 0.07 to 1.3 mm. R m increased with the snow depth from the surface to the bottom, larger than recorded in previous studies because of snow melting by solar radiation and the ILAPs (Hadley and Kirchstetter, 2012;Motoyoshi et al, 2005;Painter et al, 2013;Pedersen et al, 2015). The snow density exhibited little geographical variation across northern China at 0.13 to 0.38 g cm −3 .…”
Section: Contributions To Light Absorption By Ilapsmentioning
confidence: 57%
“…R m of the snow samples varied considerably from 0.07 to 1.3 mm. R m increased with the snow depth from the surface to the bottom, larger than recorded in previous studies because of snow melting by solar radiation and the ILAPs (Hadley and Kirchstetter, 2012;Motoyoshi et al, 2005;Painter et al, 2013;Pedersen et al, 2015). The snow density exhibited little geographical variation across northern China at 0.13 to 0.38 g cm −3 .…”
Section: Contributions To Light Absorption By Ilapsmentioning
confidence: 57%
“…A possible snow albedo reduction due to black carbon contamination was revealed by radiation measurements at the snow surface performed at Barrow, Alaska (Aoki et al, 1998(Aoki et al, , 2006, and in Japanese urban areas (Motoyoshi et al, 2005). In the case of snow and firn, a field procedure was developed, followed by further standardized lab analyses to quantify and describe black carbon presence and features (Yasunari et al, 2010).…”
Section: Previous Studies and Recent Literature On Fine Debris Occurrmentioning
confidence: 99%
“…The software used to retrieve SSA from sky-radiometer data assumes particles are spherical, although dust particles are generally nonspherical in shape. Motoyoshi et al (2005) observed broadband snow albedos in the visible and near infrared spectral regions using the snow pit method over an interval of several days, during the winters of 2001/2002 and 2002/2003 at Shinjo, Japan. The comparisons between measured albedos and theoretical ones (calculated using a radiative transfer model for atmosphere-snow systems) revealed that the snow was contaminated by strong absorptive impurities such as soot, in addition to moderate absorptive impurities such as mineral dust.…”
Section: Optical Properties Of Dustmentioning
confidence: 99%
“…Albedo of the dusted is assumed to be 0.7 (thin lines), 0.6 (thick lines) and 0.58 (gray lines), respectively (modified from Fujita, 2002 with permission from the Japanese Association for Arid Land Studies). aerosol is deposited onto the snow surface, it reduces the visible albedo that will result in a climatic change in the cryosphere due to the change in the surface energy budget of the snow cover (Nakawo and Fujita, 2005;Aoki et al, 2005a;Motoyoshi et al, 2005). Han and Nakawo (2005) reported the temporal variation of dust flux during the past 60 years using ice core samples drilled from an ice dome, 6530 m above sea level, in the Chongce Ice Cap in the West Kunlum Mountains.…”
Section: Cryosphere and Dust Interactionmentioning
confidence: 99%